Effects of strip-tillage on soil microbial community structure and function in black soil - Yuan, Cunxia; Ma, Zhixing; Liu, Siyang; Nie, Hongli; Feng, Guozhong; Wang, Shaojie; Luo, Shasha (Frontiers in Microbiology, 2025)
IntroductionThe spatial heterogeneity introduced by strip tillage (ST; maize belt (ST-M) and straw belt (ST-S)) leads to the pronounced differentiation in soil properties. However, its effects on soil microbial community structure and function remain unclear.MethodsIn this study, amplicon sequencing (Accu16S™ and AccuITS™) was used to investigate the effects of different tillage practices on soil microbial communities.ResultsThe results showed that the ST and ST-S treatments significantly increased the Shannon diversity index of microbial communities compared to rotary tillage (RT). Tillage practices also influenced microbial community structure, with fungal communities showing a more pronounced response than bacterial communities. Compared to the RT treatment, the ST-M, ST-S, and ST treatments significantly increased the relative abundance (RA) of Gemmatimonadetes and reduced the RA of Acidobacteria. Additionally, the ST-S and ST treatments significantly enhanced the absolute abundances (AAs) of Arenimonas and Luteolibacter compared to the RT treatment. Following freeze–thaw events, the ST-M, ST-S, and ST treatments significantly increased the AAs of Latescibacteria, while significantly increasing the AA of Microvirga compared to the RT treatment. Furthermore, Mantel test showed that soil bacterial communities were significantly correlated with electric conductivity (EC) and available potassium, while soil fungal communities were significantly correlated with EC and soil organic carbon. Functional prediction revealed that ST significantly promoted nitrification, denitrification, sulfur oxidation, and ectomycorrhizal.DisscussionTherefore, strip tillage could improve microbial community diversity and microbial regulation of the N and S cycles in black soil, providing a microbiological perspective for conservation agriculture.